Concept and Management of Saman-e-Mufrat (Obesity) in Unani Medicine - Azhar, Misbahuddin; Anjum, Nighat (Indian Journal of Integrative Medicine, 2021)
Saman-e-Mufrat (Obesity) is defined as a condition of abnormal excessive fat accumulation in adipose tissue due to enlargement of fat cell in size or its number or in combination upto the extent that health is impaired. According to Unani classical literature Saman-e-Mufrat (obesity) is an ancient recognized disease. According to Unani philosophy it is a Balghami Marz (disease due to phleghm) mentioned under the heading of Farbahi, which means Motapa (obese). Unani scholars has discussed predisposing factors, clinical picture and safe, effective medication (single and compound) by medicine along with some Tadbeer (regimens) e.g. Hammam (Turkish bath), Ilaj bil Ghiza (Dietotherapy), Riyazat (physical exercise) and other procedures to keep body healthy and fit.